EFEKTIVITAS DOSIS EKSTRAK BIJI KARET (Havea brasiliensi) TERHADAP KEBERHASILAN ANESTESI BENIH IKAN KOI (Cyprinus carpio) - Rani, Huna Selfia; Putriningtias, Andika; Febri, Suri Purnama (JURNAL PERIKANAN TROPIS, 2024)
Koi fish (Cyprinus carpio) is a type of freshwater ornamental fish that is in great demand because it has an attractive color pattern. Seed transportation activities are generally carried out at high densities which can cause fish to become stressed to the point of death. Prior to transportation, it is necessary to have anesthetic activities to find out how long the fish survive with a certain dose. The use of natural anesthetic substances has been widely used, one of which is rubber seed extract (Havea brasiliensi). The purpose of this study was to determine the effectiveness of rubber seed extract on the success of koi fish seeds. The research was conducted in January 2023. The research method used a completely randomized design, consisting of 4 treatments and 4 replications. The results of this study showed that the higher the concentration of rubber seed extract given, the faster the test fish fainted. Whereas for the survival of koi fish seeds in the highest anesthetic success test, P1 (control) was 100% because at P1 no treatment was given, and the lowest result was in treatment P4 (5ml/L) of 62%.Keywords: Anesthesia, Rubber seeds, koi fish, oxygen consumption rate